Perspectiva interamericana sobre la afectación de la libertad de menores en procedimientos migratorios (2016)
In its recent consultative opinion on the “Rights and Guarantees of Boys and Girls Within The Context of Migrations and/or the Need for International Protection”, the Inter-American Court of Human Rights has expounded upon the state of Inter- American law as regards the migration of minors. One of the themes of the opinion, and taken up in this article, relates to the possibility and conditions under which the liberty of minors is affected in relation to migration proceedings. Even though the solutions given by the Court are a testimony to the strong expansion of human rights, more technical precision would have been desirable in the decision.